Krok po kroku:
[tex]b_1=\frac14\\ \\ b_{n+1}=b_n^2*4^n\\ b_2=b_1^2*4^1\\ b_2=(\frac14)^2*4\\ b_2=\frac1{16}*4=\frac14\\ \\ b_3=b_{2+1}=b_2^2*4^2\\ b_3=(\frac14)^2*4^2\\ b_3=\frac1{4^2}*4^2=1\\ \\ b_4=b_{3+1}=b_3^2*4^3\\ b_4=1^2*4^3=1*4^3=4^3\\\\ \\ b_5=b_{4+1}=b_4^2*4^4\\ b_5=(4^3)^2*4^4\\ b_5=4^6*4^4=4^{10}[/tex]
Wyprowadzenie wzoru:
[tex]a_2=a_1^2*4\\ a_3=a_2^2*4^2\\ a_3=(a_1^2*4)^2*4^2\\ a_3=a_1^4*4^2+4^2\\ a_3=a_1^4*4^4\\ \\ a_4=a_3^2*4^3\\ a_4=(a_1^4*4^4)^2*4^3\\ a_4=a_1^8*4^8*4^3\\ a_4=a_1^8*4^{11}\\\\ a_5=a_4^2*4^4\\ a_5=(a_1^8*4^{11})^2*4^4\\ a_5=a_1^{16}*4^{22}*4^4\\ a_5=a_1^{16}*4^{26}\\ \\ a_5=(\frac14)^{16}*4^{26}\\ a_5=\frac1{4^{16}}*4^{26}\\ a_5=4^{10}[/tex]